Pengaruh Locus of Control terhadap Kinerja Auditor di Inspektorat Provinsi Gorontalo (Journal of Technopreneurship on Economics and Business Review, 2022)
The purpose of this study is to determine how much influence the locus of control, which consists of an internal and an external locus of control, has on the performance of auditors in the Inspectorate of Gorontalo Province, simultaneously and partially. This research is quantitative, using purposive sampling as a sampling technique based on certain characteristics that characterize the main population. Data collection was carried out by distributing questionnaires, which were tested for validity and reliability, and using path analysis as a method of data analysis. The test results show that internal and external locus of control simultaneously have a positive and significant effect on the performance of auditors at the Inspectorate of Gorontalo Province by 0.765 (76.5%), and as much as 0.235 (23.5%) is influenced by other variables not examined. Internal locus of control partially has a positive and significant effect on the performance of auditors at the Inspectorate of Gorontalo Province of 0.530 (53%), and external locus of control partially has a positive but not significant effect on the performance of auditors at the Inspectorate of Gorontalo Province of 0.390 (39%).